Three-Dimensional Anisotropic Electrical Resistivity of PEM Fuel Cell Transport Layers as Functions of Compressive Strain. Issue 3 (1st January 2015) - Todd, Devin; Schwager, Maximilian; Mérida, Walter
Abstract : We report on a method and apparatus for the determination of the three-dimensional electronic resistance of proton-exchange membrane fuel cell porous transport layers (PTLs) as a function of compression. Attention is given to the anisotropic nature of the fiber-based materials; between through- and in-plane directions and the differences within in-plane. For the first time, in-plane resistivities are resolved as functions of strain with a square four-point probe (4PP) arrangement; these are acquired in multiple directions to determine principal components of resistivity. Through-plane information is acquired with a linear 4PP apparatus with parallel capture of sample stress and strain. Results are presented for a selection of PTLs of different PTFE contents and thicknesses. In-plane resistivities exhibit linear decreases in resistivity with increasing compressive strains. We estimate an order of magnitude lower resistivity in- versus through-plane. Further, we reinforce that anisotropy in-plane undermines reports based on two or less measurements. Three methods are presented and contrasted for analyzing data in the through-plane direction. We demonstrate the limitations of common assumptions regarding contact resistances and of using PTLs of different thicknesses. It is proposed a total area resistance approach is presently the most accessible and communicable for the fuel cell community.